2009
DOI: 10.1128/jb.00824-09
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Hydrolase in Brevundimonas diminuta Is Targeted to the Periplasmic Face of the Inner Membrane by the Twin Arginine Translocation Pathway

Abstract: A twin arginine translocation (Tat) motif, involved in transport of folded proteins across the inner membrane, was identified in the signal peptide of the membrane-associated organophosphate hydrolase (OPH) of Brevundimonas diminuta. Expression of the precursor form of OPH carrying a C-terminal His tag in an opd-negative background and subsequent immunoblotting with anti-His antibodies showed that only the mature form of OPH associated with the membrane and that the precursor form of OPH was entirely found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…OPH signal peptide has a twin arginine translocation (Tat) motif, which is involved in the transportation of the folded protein across the bacterial inner membrane (Gorla et al . ). The complete opd gene along with its native signal peptide was codon optimized and used for functional secretion of OPH into the extracellular medium of E. coli .…”
Section: Resultsmentioning
confidence: 97%
“…OPH signal peptide has a twin arginine translocation (Tat) motif, which is involved in the transportation of the folded protein across the bacterial inner membrane (Gorla et al . ). The complete opd gene along with its native signal peptide was codon optimized and used for functional secretion of OPH into the extracellular medium of E. coli .…”
Section: Resultsmentioning
confidence: 97%
“…Twin-arginine signal peptides serve to target proteins to the twin-arginine protein transport (Tat) pathway, which translocates folded proteins across the bacterial cytoplasmic membrane (14). Proteinase K treatment confirmed that OPH is exported to the periplasmic side of the inner membrane in Brevundimonas diminuta and dependence on the Tat pathway was demonstrated because substitution of the invariant arginine residues of the Tat signal peptide affected both processing and localization of OPH (15). However, the mechanism by which OPH is anchored to the inner membrane and the physiological role of OPH are currently unclear.…”
mentioning
confidence: 91%
“…In bacteria these usually have either a single transmembrane domain at the C terminus (35) or an N-terminal non-cleaved twin-arginine signal anchor sequence (37). However, bioinformatic analysis supported by structural studies show that OPH has no C-terminal hydrophobic helical domain (38) and the N-terminal signal peptide of OPH is cleaved off during biosynthesis and therefore cannot serve as a signal anchor (15).…”
Section: Oph Is Tightly Bound To the B Diminuta Inner Membrane-mentioning
confidence: 99%
See 2 more Smart Citations